Rights of maintenance for grandparents and other relatives under Islamic law in Malaysia - Zainunnisaa Abd. Rahman, (Fakulti Undang - Undang, 2000)

(untitled)
Maintenance or nafqat is the plural for the word nafaqah. It means something which is given by a person of which he himself requires and needed by another consisting of food, drinks and others. These may also include clothing and lodging. Under Islamic law, it is incumbent upon family members to maintain each other mutually. The rule being that one party is in need while the other has the means to offer aid. A father, for instance, is to provide for his children, Equally, children are also to maintain their indigent parents. However, not much has been deliberated upon the right of a grandparent to receive support from his grandchild and vice versa, in Malaysia. Little is made known to the masses that a sibling is required to provide for a needy sibling, an uncle has a similar obligation towards a poor nephew and so forth. The right to be supported, however, does not include every family member for this is certainly impracticable and burdensome. Distant relatives therefore are naturally excluded. Difference of religion will also affect the right to receive support and it is also dependent on the closeness of one’s relationship to the provider. Still, jurists hold different views on the said matters. This article therefore will look into the rights of grandparents, grandchildren and other relatives to acquire maintenance under the different schools of Islamic law. Reference will also be made to the Islamic Family Law (Federal Territories) Act 1984, hereinafter referred to as Act 303 in discussing the law in Malaysia as the provision in the said Act relating to maintenance of relatives is similar to the provision in the other states